Effectiveness of Protection and Recovery Implementation for Child Victims of Sexual Violence - Achmad Arifulloh (Faculty of Law, Universitas Pekalongan, 2021)
In its development, the criminal justice system in Indonesia only positions child victims of sexual violence as reporters and witnesses. This is clearly unfair to victims who suffer material and non-material losses. The urgency of this research is that the regulation of restitution for child victims of sexual violence has resulted in the violation of rights and justice for children victims of sexual violence. This article aims to determine and analyze the effectiveness of implementing restitution for child victims of sexual violence. The type of approach used is the normative juridical method. The results of the research show that the effectiveness of implementing the protection and recovery of child victims of sexual violence has not been effective, This is due to the lack of implementation of restitution for child victims of sexual violence which ultimately also hinders the implementation of rehabilitation for child victims of sexual violence. The obstacles that influence this are legal regulations which still do not explicitly and clearly contain the implementation of restitution. This culturally also hinders the system of implementing restitution for child victims of sexual violence. Solutions that can be implemented are efforts to provide counseling, improve facilities and infrastructure in efforts to prevent and eradicate sexual abuse against children, the need for a safe house for child victims of sexual abuse during the legal process, provide understanding to victims regarding their rights, and it is necessary to regulate the amount of restitution for child victims of sexual violence.